2016
DOI: 10.21003/ea.v160-10
|View full text |Cite
|
Sign up to set email alerts
|

The system of marketing information management: development, assessment, improvement

Abstract: Abstract. The development of modern economy highlights the role and importance of information factor while making managerial decisions especially in the sphere of marketing activity of any organisation. Under such circumstances the problem of forming effective marketing information systems is becoming crucially important for Russian organisations. Marketing analysis is rather poor in modern Russian economy mainly because the history of Russian market economy is not so long and the analysis does not have enough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Song et al ( 2018) believe that MIS achieve specific goals by collecting data that the organization receives and processing it into information, and then reaching outputs and feedback. These processes according to Ashmarina and Zotova (2016) are somewhat like their existence as a control tool for each of the inputs, outputs, and feedback by not exceeding the limits of the system and taking data from the internal and external environments, strengths and identifying weaknesses and addressing them by relying on accuracy, comprehensiveness, and appropriateness. Zheng (2016) indicated that the marketing effect of MIS stems from the ability of these systems to organize and process data and present them in the form of reports to the management, which helps in taking an approach decision based on information that is identical to reality and appropriate to the nature of the studied market.…”
Section: Mis In Marketing Fieldmentioning
confidence: 99%
“…Song et al ( 2018) believe that MIS achieve specific goals by collecting data that the organization receives and processing it into information, and then reaching outputs and feedback. These processes according to Ashmarina and Zotova (2016) are somewhat like their existence as a control tool for each of the inputs, outputs, and feedback by not exceeding the limits of the system and taking data from the internal and external environments, strengths and identifying weaknesses and addressing them by relying on accuracy, comprehensiveness, and appropriateness. Zheng (2016) indicated that the marketing effect of MIS stems from the ability of these systems to organize and process data and present them in the form of reports to the management, which helps in taking an approach decision based on information that is identical to reality and appropriate to the nature of the studied market.…”
Section: Mis In Marketing Fieldmentioning
confidence: 99%
“…However, all conceptualizations appear to converge upon the common definitional consensus that MKIS are management information systems (MIS) formulated specifically to support a firm's marketing strategy and decision-making (Mandal, 2018;Wahyuni & Lestari, 2020). Accordingly, the quintessential MIS contains four core components, namely, internal reporting systems that organize and collate a firm's internal records with immediate value to marketing decisions; marketing research systems, which 2 are constituted of monitoring and tracking exercises designed purposefully to address well-defined marketing problems; marketing intelligence systems consisted of data sources and procedures to extract decision-making information from the marketing environment; and, fourthly, marketing models that act as the mechanism for interpreting marketing intelligence for application to strategic marketing (Ashmarina & Zotova, 2016;Sigauke, 2019;Martell, 2018). MKIS are particularly necessary for contemporary organizations because these systems provide the most effective frameworks for monitoring changes within the external market environment, such as shifting factors of consumer behavior, industry competition, government policies, technology, and economic conditions (Perreault, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The main objectives of information support on standardization documents in an industrial enterprise (organization) is timely and thorough provision of relevant regulatory documents. In order to purchase regulatory documents on a regular basis, maintain their life cycle and provide information support for deliveries and product life cycle, the following tasks have to be solved: different types of information should be categorized in the enterprise, the notion of a marketing information system should be defined, methods should be selected to evaluate the efficiency of information support in the enterprise and a model of an efficient management information system should be created [1]. It is possible to solve the above tasks successfully in case regulatory documents are provided in a synchronized way with the terms of contract obligations of the enterprise (organization).…”
Section: Introductionmentioning
confidence: 99%